2016
DOI: 10.5194/wes-1-205-2016
|View full text |Cite
|
Sign up to set email alerts
|

Wind tunnel tests with combined pitch and free-floating flap control: data-driven iterative feedforward controller tuning

Abstract: Abstract. Wind turbine load alleviation has traditionally been addressed in the literature using either full-span pitch control, which has limited bandwidth, or trailing-edge flap control, which typically shows low control authority due to actuation constraints. This paper combines both methods and demonstrates the feasibility and advantages of such a combined control strategy on a scaled prototype in a series of wind tunnel tests. The pitchable blades of the test turbine are instrumented with free-floating fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…For other experiments executed with this turbine, see e.g. Van Solingen et al (2014) The blades used for this experiments are designed and presented in (Navalkar et al, 2016) and is shown in on the blades, which relates directly to the out-of-plane bending moments.…”
Section: Wind Turbinementioning
confidence: 99%
See 1 more Smart Citation
“…For other experiments executed with this turbine, see e.g. Van Solingen et al (2014) The blades used for this experiments are designed and presented in (Navalkar et al, 2016) and is shown in on the blades, which relates directly to the out-of-plane bending moments.…”
Section: Wind Turbinementioning
confidence: 99%
“…For results obtained with these flaps, see e.g. Navalkar et al (2016). The experiments shown in this paper are obtained without using the piezobenders on the free-floating flaps as a control input.…”
Section: Wind Turbinementioning
confidence: 99%